2015
DOI: 10.1177/0192513x15583068
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Intention and Positive Parenting Behaviors Among First-Time Mothers

Abstract: Mothers and children often experience negative outcomes following unintended pregnancies. The current study examined for whom and under what conditions unintended pregnancy was associated with negative outcomes among a sample of 682 first-time mothers, recruited as part of the Predicting and Preventing Child Neglect in Teen Mothers study. Specifically, maternal demographic characteristics were examined as moderators of the association between pregnancy intention and parenting behaviors when children were 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…That is to say, regardless of whether the pregnancy was intended or not fathers are present and take care of their children similarly, but their pregnancy intentions may affect the amount of stimulating interaction fathers engage in with their children. Similar to prior studies conducted with mothers (Cheng et al, 2009; Claridge et al, 2017; Gauthreaux et al, 2017; Shah et al, 2011; Taylor & Cabral, 2002), it appears that fathers’ pregnancy intentions are an important factor that can ultimately influence their children’s well-being (Lamb & Tamis-LeMonda, 2004), as fathers’ involvement in early childhood supports their children’s language, cognitive, and socioemotional development (Cabrera et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…That is to say, regardless of whether the pregnancy was intended or not fathers are present and take care of their children similarly, but their pregnancy intentions may affect the amount of stimulating interaction fathers engage in with their children. Similar to prior studies conducted with mothers (Cheng et al, 2009; Claridge et al, 2017; Gauthreaux et al, 2017; Shah et al, 2011; Taylor & Cabral, 2002), it appears that fathers’ pregnancy intentions are an important factor that can ultimately influence their children’s well-being (Lamb & Tamis-LeMonda, 2004), as fathers’ involvement in early childhood supports their children’s language, cognitive, and socioemotional development (Cabrera et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…This study contributes to the literature on pregnancy intendedness and postnatal bonding in several key ways. First, recent studies that examined the association between pregnancy intendedness and postnatal mother–child relationships often use a dichotomous measure of unplanned/planned or unintended/intended despite acknowledging the multidimensional nature of pregnancy intendedness (e.g., Boden et al., 2015; Claridge et al., 2017; Nelson & O'Brien, 2012). Our measure also captured pregnancies reported as unwanted—which tend to be associated with worse outcomes than those that are reported as mistimed.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate was 55% by the end of the study at 36 months. An attrition analyses performed on these data revealed that the participants who dropped out by 18 months were not significantly different than those who remained in the study in terms of age, relationship status, race, or education (Claridge et al, 2017). Average maternal age at birth was 21.2 years (s.d.…”
Section: Methodsmentioning
confidence: 99%